P549 Oxidative stress and antioxidant capacity biomarkers in adults and children with IBD: current update from OxIBDiet trial. (21st January 2022) - Quattrini, S; Gatti, S; Palpacelli, A; Mattioli, S; Cianfruglia, L; Galezzi, T; Monachesi, C; Quatraccioni, C; Catassi, G; Di Sario, A; Armeni, T; Catassi, C
Abstract: Background: Oxidative stress takes part in the pathogenesis of inflammatory bowel disease (IBD). The OxIBDiet (NCT04513015) is a multicentre ongoing project designed to evaluate oxidative status of IBD children and adults and to estimate the effects of an antioxidant diet in a subgroup of IBD patients. Methods: The total antioxidant capacity, measured through the ferric reducing ability of plasma (FRAP, µmol/equivalent FeSO4) and oxygen radical absorbance capacity (ORAC, plasma trolox equivalents), lipid peroxidation, as serum levels of the thiobarbituric acid reactive substances (TBARs, µmol MDA) and the degree of protein oxidation, as advanced Oxidation Protein Products (AOPP, µmol/g protein), were measured. Activities (nmol/min/mg of protein) of the main antioxidant enzymes, superoxide dismutase (SOD), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione S-Transferase (GST) and catalases (CAT) were evaluated in PMNs cells and plasma. Oxidative biomarkers were correlated with clinical parameters. Results: Twenty-three adults (mean age: 33, 7, IQR 20, 5 years, 42% male, 63% in remission) and 41 children with IBD (mean age: 12, IQR 4 years, 52% male, 61% in remission) were enrolled and compared respectively to 29 adults and 23 children controls. FRAP was significantly reduced in IBD children compared to adults (202 vs 277 mcmol/eq FeSO4, p<0.0001) and was correlated with age (r=0.5718; p<0.0001). Plasmatic ORAC was significantly higher in IBD children compared to controls and adults with IBD (Figure 1). ORAC in IBD subjects resulted inversely correlated to age (r= -0.4417, p=0.0004) and use of biologics (r= -0.4246, p=0.0006). AOPP were elevated in paediatric IBD versus controls (p=0.0049) and correlated to the diagnosis of Crohn at the multiple regression analysis (r=-0.732; p=0.023). The main antioxidant enzymes plasmatic activities are shown in table 1. Conclusion: The antioxidant system and therefore the antioxidant capacity is significantly different in IBD compared to controls and evolve from paediatric to adult age, maybe as an effort to compensate the persistent redox imbalance and inflammation. Involvement of antioxidant cascade in IBD pathogenesis and role in therapeutic approach will be better outlined by the final results.